Negative electrode material, preparation method thereof and lithium ion battery

By using a carbon matrix material with pores in the negative electrode material of a lithium-ion battery and evenly filling the silicon-based material in its holes, the problem of volume expansion of the negative electrode material during circulation is solved, and the circulation performance and stability of the battery are improved.

CN119920890APending Publication Date: 2025-05-02BTR NEW MATERIAL GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311435362.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The negative electrode material of lithium-ion batteries has a severe volume expansion effect during the circulation process, resulting in the material being powdered and broken, and the battery's circulation attenuation is very fast.

Method used

A negative electrode material including a carbon matrix material and a silicon-based material is adopted. The carbon matrix material has pores, and at least a portion of the silicon-based material is distributed in the pores of the carbon matrix material. The silicon-based material is uniformly filled in the pores of the carbon matrix material through a vapor deposition process.

Benefits of technology

Effectively suppress the volume expansion of the negative electrode material, improve the circulation performance of the negative electrode material, reduce the expansion and structural collapse of the negative electrode material, reduce the side reaction with the electrolyte, and improve the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920890A_ABST
    Figure CN119920890A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode material, a preparation method thereof and a lithium ion battery. A three-electrode type battery consisting of a negative electrode prepared from the negative electrode material as a working electrode, metal lithium as a reference electrode, metal lithium as a counter electrode and a lithium ion electrolyte is charged and discharged; obtaining a graph of the relationship between the potential V of the working electrode and a differential value (dQ / dV) obtained by differentiating the charge / discharge capacity (Q) with respect to the potential V of the working electrode on the basis of the reference electrode; in the relation curve graph of the differential value dQ / dV and the potential V, when the negative electrode material is electrified in the lithium removal direction, the differential value dQ / dV of the potential V between 200mV and 350mV has the maximum peak value A and the half-peak width F1, the differential value dQ / dV of the potential V between 380mV and 470mV has the maximum peak value B and the half-peak width F2, A > B and F2 < F1, and the relation that (B * F2) / (A * F1) is smaller than or equal to 0.35 is met. The negative electrode material provided by the invention can effectively inhibit volume expansion of the negative electrode material, and the cycle performance of the negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to negative electrode materials and preparation methods thereof, and lithium ion batteries. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, high cycle life, low environmental pollution and no memory effect, so they are widely used in electric vehicles and consumer electronic products. With the rapid development of electric vehicles in recent years, the demand for higher energy density lithium-ion batteries has been growing, which has prompted researchers to look for battery materials with higher energy density and better cycle performance. The positive and negative electrode materials are the core of the battery and determine the working efficiency of the battery. At present, the commercial negative electrode material is graphite, and its capacity is close to the theoretical upper limit, and the further improvement is limited. Therefore, there is an urgent need to develop a new generation of high energy density negative electrode materials. Among them, silicon-based negative electrode materials are generally considered to be the next generation of battery negative electrode materials, with advantages such as high capacity, abundant sources, and relative safety.

[0003] However, the silicon negative electrode has a dramatic volume expansion effect during the cycle, which causes the material to pulverize and break, and the battery cycle decays quickly. There are currently multiple solutions to this problem, including structural design of silicon, the use of nano-, porous and other technical means; improvement by composite coating and other methods; modification and improvement of silicon pole pieces by new electrolytes, adhesives, etc. Among them, nano-sizing is one of the current mainstream directions. Reducing the size of silicon to nano-size can reduce the expansion of silicon and prevent the pulverization of silicon. However, the existing nano-sizing solutions still have many shortcomings in solving the performance of silicon, and there is still a lot of room for improvement in long-cycle performance. Summary of the invention

[0004] The purpose of the present application is to provide a negative electrode material and a preparation method thereof, and a lithium-ion battery, which can effectively inhibit the volume expansion of the negative electrode material and improve the cycle performance of the negative electrode material.

[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, and at least part of the silicon-based material is distributed in the pores of the carbon-based material;

[0006] A three-electrode battery consisting of a negative electrode prepared from the negative electrode material as a working electrode, metal lithium as a reference electrode, metal lithium as a counter electrode and an electrolyte containing metal lithium ions is charged and discharged to obtain a curve graph showing the relationship between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q of the potential V of the working electrode with respect to the reference electrode and the potential V of the working electrode;

[0007] In the relationship curve diagram of the differential value dQ / dV and the potential V, when the negative electrode material is energized in the delithiation direction, the differential value dQ / dV of the potential V between 200mV and 350mV has a maximum peak value A, and the half-peak width is F1, and the differential value dQ / dV of the potential V between 380mV and 470mV has a maximum peak value B, and the half-peak width is F2, wherein A>B and F2<F1, and the relationship is satisfied: (B*F2) / (A*F1)≤0.35.

[0008] In some embodiments, the carbon matrix material includes at least one of hard carbon, soft carbon, graphite, mesophase carbon microbeads, activated carbon, porous carbon, mesoporous carbon, or carbon gel.

[0009] In some embodiments, the total pore volume of the carbon matrix material is ≥ 0.4 cm 3 / g.

[0010] In some embodiments, the pores in the carbon matrix material include micropores, and the volume proportion of the micropores in the total pore volume is ≥ 80%.

[0011] In some embodiments, the average pore size of the pores in the carbon matrix material is ≤5 nm.

[0012] In some embodiments, the silicon-based material includes at least one of amorphous silicon, crystalline silicon, silicon oxide, silicon alloy, and a composite of crystalline silicon and amorphous silicon.

[0013] In some embodiments, the average particle size of the silicon-based material is 1 nm to 500 nm.

[0014] In some embodiments, the mass content of silicon in the silicon-based material is ≥ 99%.

[0015] In some embodiments, the negative electrode material further includes a carbon layer located on the surface of the active material.

[0016] In some embodiments, the negative electrode material further includes a carbon layer located on the surface of the active material, and the carbon layer includes an amorphous carbon material.

[0017] In some embodiments, the median particle size D50 of the negative electrode material is ≤10 μm.

[0018] In some embodiments, the specific surface area of ​​the negative electrode material is ≤5m 2 / g.

[0019] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0020] providing a carbon matrix material having pores;

[0021] The carbon matrix material is vapor-deposited using a silicon source gas to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average particle size of the carbon matrix material is D μm, the average pore size of the carbon matrix material is V nm, the volume concentration ratio of the silicon source gas is H, the flow rate of the silicon source gas is NL / min, the deposition time of the vapor deposition is T h, and the deposition relationship is controlled to satisfy T*D 1 / 2 =α*V 2 *N*H, where α is the sedimentation coefficient, 0.1≤α≤1.

[0022] In some embodiments, the silicon source gas includes at least one of monosilane, disilane, monochlorosilane, and dichlorosilane.

[0023] In some embodiments, the average particle size of the carbon matrix material is 1 μm to 15 μm.

[0024] In some embodiments, the average pore size of the carbon matrix material is 0.1 nm to 5 nm.

[0025] In some embodiments, the volume concentration of the silicon source gas is 1% to 90%.

[0026] In some embodiments, the flow rate of the silicon source gas is 0.5 L / min to 100 L / min.

[0027] In some embodiments, the vapor deposition time is 0.1 h to 15 h.

[0028] In some embodiments, the deposition temperature of the vapor deposition is 300°C to 800°C.

[0029] In some embodiments, the step of providing a carbon matrix material having pores comprises: carbonizing a carbon source, and then acid-washing and activating the carbonization product to obtain the carbon matrix material having pores.

[0030] In some embodiments, the carbon source includes at least one of bamboo charcoal, coconut shell, resin, starch and fruit shell.

[0031] In some embodiments, the step of subjecting the carbonized product to acid treatment includes: subjecting the carbonized product to an acid solution with a concentration of 0.5 mol / L to 15 mol / L for 0.5 h to 20 h.

[0032] In some embodiments, the step of pickling the carbonized product includes: placing the carbonized product in an acid solution with a concentration of 0.5 mol / L to 15 mol / L for 0.5 h to 20 h, wherein the acid solution includes at least one of hydrochloric acid, nitric acid, sulfuric acid, carbonic acid, acetic acid, benzoic acid, hydrofluoric acid, oxalic acid, phosphoric acid, and carboxylic acid.

[0033] In some embodiments, the step of activating the carbonized product includes: drying the acid-washed carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation.

[0034] In some embodiments, the step of activating the carbonized product includes: drying the acid-washed carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation, wherein the concentration of the water vapor is 0.5% to 30%.

[0035] In some embodiments, the step of activating the carbonized product includes: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, the activation treatment temperature is 380°C to 2000°C, and the activation treatment time is 0.5h to 30h.

[0036] In some embodiments, the method further includes: performing carbon coating treatment on the active substance to obtain a negative electrode material having a carbon layer on the surface; the carbon coating treatment includes at least one of solid phase carbon coating, liquid phase carbon coating and gas phase carbon coating.

[0037] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or comprises the negative electrode material prepared by the negative electrode material preparation method described in the second aspect.

[0038] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0039] The negative electrode material provided in the present application includes an active substance, the active substance includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, and the capacity of the negative electrode material can be increased. When the negative electrode material is energized in the direction of lithium removal, the differential value dQ / dV of the potential V between 200mV and 350mV has a maximum peak value A, and the half-peak width is F1, and the differential value dQ / dV of the potential V between 380mV and 470mV has a maximum peak value B, and the half-peak width is F2. The width is F2, wherein A>B and F2<F1, and the negative electrode material satisfies the relationship: (B*F2) / (A*F1)≤0.35; the present application ensures that the silicon-based material is uniformly filled in the pores of the carbon-based material rather than on the surface of the carbon-based material by setting the value of (B*F2) / (A*F1) within the above range, so that the silicon-based material is uniformly filled in the pores of the carbon-based material, and at the same time, the generation of large-sized silicon-based materials can be reduced, thereby reducing the volume expansion of the negative electrode material, so that the negative electrode material has lower expansion and better cycle performance.

[0040] The preparation method of the negative electrode material provided in the present application utilizes a vapor deposition process to uniformly fill the silicon-based material in the pores of the carbon-based material to prepare the negative electrode material. By controlling the deposition conditions, the deposition of the silicon-based material on the surface of the carbon-based material can be reduced, and the silicon-based material can be effectively filled in the pores of the carbon-based material to increase the capacity of the negative electrode material. At the same time, the size and shape of the silicon-based material can be controlled to ensure that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, effectively reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and thus improve the cycle performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0042] Figure 1 The V-dQ / dV test curve of the negative electrode material provided in this application;

[0043] Figure 2 This is a scanning electron microscope (SEM) image of the negative electrode material prepared in Example 1 of the present application;

[0044] Figure 3 XRD diagram of the negative electrode material prepared in Example 1 of the present application;

[0045] Figure 4 This is the first charge and discharge curve of the negative electrode material prepared in Example 1 of the present application;

[0046] Figure 5 This is the cycle performance curve of the negative electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0047] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0048] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0050] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0051] In a first aspect, the present application provides a negative electrode material, comprising an active material, wherein the active material comprises a carbon-based material and a silicon-based material, wherein the carbon-based material has pores, and at least part of the silicon-based material is distributed in the pores of the carbon-based material;

[0052] A three-electrode battery consisting of a negative electrode prepared from the negative electrode material as a working electrode, metal lithium as a reference electrode, metal lithium as a counter electrode and an electrolyte containing metal lithium ions is charged and discharged to obtain a curve graph showing the relationship between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q of the potential V of the working electrode with respect to the reference electrode and the potential V of the working electrode;

[0053] like Figure 1 As shown in the relationship curve diagram of the dQ / dV and the potential V, when the negative electrode material is energized in the delithiation direction, the differential value dQ / dV of the potential V between 200mV and 350mV has a maximum peak value A, and the half-peak width is F1, and the differential value dQ / dV of the potential V between 380mV and 470mV has a maximum peak value B, and the half-peak width is F2, wherein A>B and F2<F1, and the negative electrode material satisfies the relationship: (B*F2) / (A*F1)≤0.35.

[0054] The negative electrode material provided by the present application includes an active substance, the active substance includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, and the capacity of the negative electrode material can be increased. When the negative electrode material is energized in the lithium removal direction, the differential value dQ / dV of the potential V between 200mV and 350mV has a maximum peak value A, and the half-peak width is F1, and the differential value dQ / dV of the potential V between 380mV and 470mV has a maximum peak value B, The half-peak width is F2, wherein A>B and F2<F1, and the negative electrode material satisfies the relationship: (B*F2) / (A*F1)≤0.35; the present application ensures that the silicon-based material is uniformly filled in the pores of the carbon-based material rather than on the surface by setting the value of (B*F2) / (A*F1) within the above range, so that the silicon-based material is uniformly filled in the pores of the carbon-based material, and at the same time, the generation of large-sized silicon-based materials can be reduced, thereby reducing the volume expansion of the negative electrode material, so that the negative electrode material has lower expansion and better cycle performance.

[0055] Specifically, the value of (B*F2) / (A*F1) can be 0.01, 0.5, 0.8, 0.1, 0.12, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.32 or 0.35, etc., and of course, it can also be other values ​​within the above range, which are not limited here. The value of (B*F2) / (A*F1) is controlled within the above range, which can ensure that the silicon-based material can be evenly filled in the pores of the carbon-based material, and the size of the silicon-based material is not too large, and the proportion of surface silicon and large-particle silicon in the negative electrode material is reduced, which can reduce the volume expansion of the negative electrode material, so that the negative electrode material has lower expansion and better cycle performance.

[0056] In some embodiments, the carbon matrix material includes at least one of hard carbon, soft carbon, graphite, mesophase carbon microbeads, activated carbon, porous carbon, mesoporous carbon, or carbon gel.

[0057] In some embodiments, the total pore volume of the carbon matrix material is ≥ 0.4 cm 3 / g, specifically 0.4cm 3 / g, 0.5cm 3 / g, 0.8cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.3cm 3 / g, 1.5cm 3 / g or 1.8cm 3 / g, etc., and of course, other values ​​within the above range may also be used, which are not limited here. Preferably, the total pore volume of the carbon matrix material is ≥0.5cm 3 / g; further preferably, the total pore volume of the carbon matrix material is ≥0.7cm 3 / g.

[0058] In some embodiments, the pores of the carbon matrix material include micropores, and the proportion of the micropores is ≥80%. Specifically, the proportion of the micropores can be 80%, 82%, 85%, 88%, 90%, 92%, 93%, 95%, 98% or 99%, etc., which are not limited here. It can be understood that the size of the silicon-based material deposited in the pores of the carbon matrix material is determined by the size of the pores. The higher the proportion of micropores, the smaller the average pore size of the pores of the carbon matrix material, and the smaller the particle size of the silicon-based material deposited in the pores of the carbon matrix material. The particle size of the silicon-based material deposited in the pores of the carbon matrix material is small, and the volume expansion of the negative electrode material during the cycle is small, which is beneficial to improve the cycle performance of the negative electrode material. Preferably, the proportion of micropores is ≥90%; further preferably, the proportion of micropores is ≥95%.

[0059] In some embodiments, the average pore size of the pores of the carbon matrix material is ≤5nm, and can be 0.1nm, 0.5nm, 1nm, 1.5nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm or 5nm, etc., and can also be other values ​​within the above range, which are not limited here. Preferably, the average pore size of the pores of the carbon matrix material is ≤2nm; more preferably, the average pore size of the pores of the carbon matrix material is ≤1.8nm.

[0060] In some embodiments, the silicon-based material includes at least one of amorphous silicon, crystalline silicon, silicon oxide, silicon alloy, and a composite of crystalline silicon and amorphous silicon.

[0061] In some embodiments, the average particle size of the silicon-based material is 1 nm to 500 nm, specifically 1 nm, 5 nm, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 300 nm, 350 nm, 400 nm or 500 nm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Preferably, the average particle size of the silicon-based material is 1 nm to 50 nm; more preferably, the average particle size of the silicon-based material is 1 nm to 10 nm.

[0062] In some embodiments, the mass content of silicon in the silicon-based material is ≥ 99%.

[0063] In some embodiments, the negative electrode material further includes a carbon layer located on the surface of the active material. It can be understood that the carbon layer can act as a buffer layer to reduce the volume expansion effect of the negative electrode material to a certain extent, while enhancing the conductivity of the negative electrode material; the carbon layer can also reduce the direct contact between the silicon-based material and the electrolyte, inhibit the excessive growth of the SEI film on the surface of the negative electrode material, stabilize the interface of the negative electrode material, and improve the coulombic efficiency of the negative electrode material.

[0064] In some embodiments, the negative electrode material further includes a carbon layer located on the surface of the active material, and the carbon layer includes an amorphous carbon material.

[0065] In some embodiments, the median particle size D50 of the negative electrode material is ≤10 μm, and can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., and can also be other values ​​within the above range, which is not limited here. Controlling the median particle size of the negative electrode material within the above range is conducive to improving the cycle performance of the lithium-ion battery made of the negative electrode material.

[0066] In some embodiments, the specific surface area of ​​the negative electrode material is ≤5m 2 / g, specifically 0.1m 2 / g, 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g or 5m 2 / g, etc., and of course, it can also be other values ​​within the above range, which is not limited here. Controlling the specific surface area of ​​the negative electrode material within the above range is beneficial to improving the initial efficiency and cycle performance of the lithium battery made of the negative electrode material.

[0067] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0068] Step S100, providing a carbon matrix material having pores;

[0069] Step S200, using silicon source gas to perform vapor deposition on the carbon matrix material to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average particle size of the carbon matrix material is D μm, the average pore size of the carbon matrix material is V nm, the volume concentration ratio of the silicon source gas is H, the flow rate of the silicon source gas is NL / min, the deposition time of the vapor deposition is T h, and the deposition relationship is controlled to satisfy T*D 1 / 2 =α*V 2 *N*H, where α is the sedimentation coefficient, 0.1≤α≤1.

[0070] The preparation method of the negative electrode material provided in the present application utilizes a vapor deposition process to uniformly fill the silicon-based material in the pores of the carbon-based material to prepare the negative electrode material. By controlling the deposition conditions, the deposition of the silicon-based material on the surface of the carbon-based material can be reduced, and the silicon-based material can be effectively filled in the pores of the carbon-based material to increase the capacity of the negative electrode material. At the same time, the size and shape of the silicon-based material can be controlled to ensure that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, effectively reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and thus improve the cycle performance of the negative electrode material.

[0071] Step S100: providing a carbon matrix material having pores.

[0072] It should be noted that the carbon matrix material with pores in the present application can be purchased and used directly, or can be prepared by carbonizing a carbon source, which is not limited here.

[0073] In some embodiments, the step of providing a carbon matrix material having pores comprises: carbonizing a carbon source, and then subjecting a carbonization product to an acidification treatment and an activation treatment to obtain a carbon matrix material having pores.

[0074] In some embodiments, the carbon source comprises at least one of bamboo charcoal, coconut shell, resin, starch and fruit shell.

[0075] In some embodiments, the step of subjecting the carbonized product to acid treatment includes: subjecting the carbonized product to an acid solution with a concentration of 0.5 mol / L to 15 mol / L for 0.5 h to 20 h.

[0076] Specifically, the concentration of the acid solution can be 0.5 mol / L, 1 mol / L, 3 mol / L, 5 mol / L, 7 mol / L, 9 mol / L, 10 mol / L, 12 mol / L, 14 mol / L or 15 mol / L, etc., and is not limited here.

[0077] The time for placing the carbonized product in the acid solution can be 0.5h, 0.8h, 1h, 2h, 3h, 5h, 8h, 12h, 15h, 18h or 20h, etc., which is not limited here.

[0078] In some embodiments, the step of pickling the carbonized product includes: placing the carbonized product in an acid solution with a concentration of 0.5 mol / L to 15 mol / L for 0.5 h to 20 h, wherein the acid solution includes at least one of hydrochloric acid, nitric acid, sulfuric acid, carbonic acid, acetic acid, benzoic acid, hydrofluoric acid, oxalic acid, phosphoric acid, and carboxylic acid.

[0079] In some embodiments, the step of activating the carbonized product includes: drying the pickled carbonized product and placing it in a mixture of nitrogen and water vapor for activation. It can be understood that pickling and activation treatment are beneficial to the directional deposition of silicon-based materials into the pores of the carbon-based material during the subsequent silicon deposition process, thereby reducing the deposition of silicon-based materials on the surface of the carbon-based material.

[0080] In some embodiments, the step of activating the carbonized product includes: drying the pickled carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation, wherein the concentration of the water vapor is 0.5% to 30%. The concentration of the water vapor can be 0.5%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25% or 30%, etc., which is not limited here.

[0081] In some embodiments, the step of activating the carbonized product includes: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, the activation treatment temperature is 380°C to 2000°C, and the activation treatment time is 0.5h to 30h.

[0082] Specifically, the temperature of the activation treatment may be 380°C, 400°C, 500°C, 800°C, 1000°C, 1200°C, 1500°C, 1800°C or 2000°C, etc., which is not limited here. The time of the activation treatment may be 0.5h, 1h, 3h, 5h, 8h, 10h, 12h, 15h, 18h, 24h or 30h, etc., which is not limited here.

[0083] In some embodiments, the temperature of the carbonization treatment is 400° C. to 2000° C., and the time of the carbonization treatment is 3 h to 30 h.

[0084] Specifically, the temperature of the carbonization treatment may be 400°C, 500°C, 600°C, 800°C, 1000°C, 1200°C, 1500°C, 1800°C or 2000°C, etc., which is not limited here. The time of the carbonization treatment may be 3h, 5h, 8h, 12h, 15h, 18h, 24h, 28h or 30h, etc., which is not limited here.

[0085] Step S200, using silicon source gas to perform vapor deposition on the carbon matrix material to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average particle size of the carbon matrix material is D μm, the average pore size of the carbon matrix material is V nm, the volume concentration ratio of the silicon source gas is H, the flow rate of the silicon source gas is NL / min, the deposition time of the vapor deposition is T h, and the deposition relationship is controlled to satisfy T*D 1 / 2 =α*V 2 *N*H, where α is the sedimentation coefficient, 0.1≤α≤1.

[0086] Specifically, the value of α can be 0.1, 0.3, 0.5, 0.65, 0.7, 0.78, 0.89, 0.92, 0.98 or 1, etc., and is not limited here.

[0087] In some embodiments, the silicon source gas includes at least one of monosilane, disilane, monochlorosilane, and dichlorosilane.

[0088] In some embodiments, the average particle size of the carbon matrix material is 1 μm to 15 μm, specifically 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0089] In some embodiments, the average pore size of the carbon matrix material is 0.1nm to 5nm, specifically 0.1nm, 0.5nm, 1nm, 1.5nm, 2nm, 3nm, 3.7nm, 4nm, 4.5nm, 4.8nm or 5nm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] In some embodiments, the volume concentration of the silicon source gas is 1% to 90%, specifically 1%, 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0091] In some embodiments, the flow rate of the silicon source gas is 0.5L / min to 100L / min, specifically 0.5L / min, 1L / min, 5L / min, 10L / min, 20L / min, 30L / min, 50L / min, 70L / min, 85L / min, 95L / min or 100L / min, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0092] In some embodiments, the deposition time of the vapor deposition is 0.1 h to 15 h, specifically 0.1 h, 0.5 h, 1 h, 3 h, 5 h, 8 h, 10 h, 12 h, 13 h, 14 h or 15 h, etc., which is not limited here.

[0093] In some embodiments, the deposition temperature of the vapor deposition is 300°C to 800°C, specifically 300°C, 400°C, 500°C, 600°C, 650°C, 700°C, 750°C or 800°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0094] In some embodiments, the method further includes: performing carbon coating treatment on the active substance to obtain a negative electrode material having a carbon layer on the surface; the carbon coating treatment includes at least one of solid phase carbon coating, liquid phase carbon coating and gas phase carbon coating.

[0095] In some embodiments, the carbon coating treatment step specifically includes: heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material having a carbon layer on the surface.

[0096] In some embodiments, the carbon coating treatment step specifically includes: heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material having a carbon layer on the surface, wherein the carbon source gas is a hydrocarbon.

[0097] In some embodiments, the carbon coating treatment step specifically includes: heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material having a carbon layer on the surface, wherein the carbon source gas includes at least one of methane, ethylene, acetylene, propyne, propylene, propane, toluene, benzene, styrene and phenol.

[0098] In some embodiments, the carbon coating treatment step specifically includes: after heating the active material, introducing a protective gas and a carbon source gas, and thermally cracking the carbon source gas to obtain a negative electrode material with a carbon layer on the surface, wherein the thermal cracking temperature is 600°C to 1000°C, and the thermal cracking time is 30min to 24h.

[0099] The temperature of thermal cracking can be 600°C, 650°C, 680°C, 700°C, 780°C, 800°C, 900°C, 960°C or 1000°C, etc., and the time of thermal cracking can be 30 min, 1 h, 3 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h or 24 h, etc., which are not limited here.

[0100] In some embodiments, the carbon coating step specifically includes: carbonizing a mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material having a carbon layer on the surface.

[0101] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the carbonization temperature is 500°C to 1000°C, and the carbonization time is 30min to 24h.

[0102] Specifically, the temperature of the carbonization treatment may be 600°C, 650°C, 680°C, 700°C, 780°C, 800°C, 900°C, 960°C or 1000°C, etc., which is not limited here. The time of the carbonization treatment may be 30 min, 1 h, 3 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h or 24 h, etc., which is not limited here.

[0103] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material having a carbon layer on the surface, wherein the solid carbon source includes at least one of sugars, esters, hydrocarbons, organic acids and high molecular polymers.

[0104] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the solid carbon source includes at least one of polyvinyl chloride, polyvinyl butyral, polyacrylonitrile, polyacrylic acid, polyethylene glycol, polypyrrole, polyaniline, sucrose, glucose, maltose, citric acid, asphalt, furfural resin, epoxy resin and phenolic resin.

[0105] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a solid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the mass ratio of the solid carbon source to the active substance is (1-50): (20-100), specifically 1:99, 10:90, 20:80, 30:70 or 50:50, etc., which is not limited here.

[0106] In some embodiments, the carbon coating step specifically includes: carbonizing a mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material having a carbon coating layer on the surface.

[0107] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the mass ratio of the liquid carbon source to the active substance is (1-50): (20-100), specifically 1:99, 10:90, 20:80, 30:70 or 50:50, etc., which is not limited here.

[0108] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the liquid carbon source includes at least one of n-hexane, toluene, benzene, xylene, methanol, ethanol, propanol, butanol, pentanol, acetone, butanone, 2-pentanone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate and pentyl acetate.

[0109] In some embodiments, the carbon coating step specifically includes: carbonizing the mixture obtained by mixing the active substance with a liquid carbon source to obtain a negative electrode material with a carbon layer on the surface, wherein the carbonization temperature is 600°C to 1200°C, and the carbonization time is 2h to 20h.

[0110] Specifically, the temperature of the carbonization treatment may be 600°C, 650°C, 700°C, 800°C, 900°C, 1000°C or 1200°C, etc., which is not limited here.

[0111] The carbonization treatment time can be 2 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h or 20 h, etc., which is not limited here.

[0112] In some embodiments, the carbon coating process is performed under a protective atmosphere, wherein the protective atmosphere includes at least one of nitrogen, helium, neon, argon, and krypton.

[0113] In some embodiments, the method further includes: shaping, screening and grading the carbon-coated product to obtain a negative electrode material having a carbon layer on the surface, wherein the shaping includes at least one of crushing, grinding, ball milling and gas crushing.

[0114] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or comprises the negative electrode material prepared by the negative electrode material preparation method described in the second aspect.

[0115] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0116] Example

[0117] Example 1

[0118] (1) The bamboo charcoal was carbonized at 800°C for 16 h, and then the carbonized product was treated with 6 mol / L hydrochloric acid for 5 h. After drying, a mixed gas of water vapor and nitrogen (water vapor concentration was 7.8%) was introduced, and the temperature was raised to 780°C and activated for 24 h to obtain a carbon matrix material with an average pore size of 2.1 nm and an average particle size of 10 μm.

[0119] (2) The carbon matrix material is placed in a chemical vapor deposition (CVD) device, silane is introduced into the CVD device at a rate of 22 L / min, the volume concentration of silane is controlled to be 50%, and then the temperature is raised to 600°C, and a vapor deposition reaction is carried out for 4 hours to obtain an active substance.

[0120] (3) The active substance and the phenolic resin were mixed in a mass ratio of 50:15, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 720° C. for 2 h.

[0121] (4) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.

[0122] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is amorphous silicon, the average particle size of the silicon-based material is 2.3 nm, and the specific surface area of ​​the negative electrode material is 3.4 m 2 / g, and the median particle size is 9.8μm.

[0123] The deposition coefficient α of the vapor deposition in this embodiment is 0.26.

[0124] Figure 2 This is a scanning electron microscope (SEM) image of the negative electrode material prepared in Example 1 of the present application.

[0125] Figure 3 The XRD pattern of the negative electrode material prepared in Example 1 of the present application is as follows: Figure 3 As shown, the silicon-based material in the negative electrode material is amorphous.

[0126] Figure 4 This is the first charge and discharge curve of the negative electrode material prepared in Example 1 of the present application, such as Figure 4 As shown, the first charge and discharge capacity of the negative electrode material is as high as 2098 mAh / g, and the first efficiency is also as high as 93.1%.

[0127] Figure 5 The cycle performance curve of the negative electrode material prepared in Example 1 of the present application is as follows: Figure 5 As shown, the negative electrode material has excellent cycle performance, and the capacity retention rate after 50 cycles is 92.2%.

[0128] Example 2

[0129] (1) A commercial carbon matrix material with an average pore size of 1.9 nm and an average particle size of 4 μm was placed in a chemical vapor deposition (CVD) device, and silane was introduced into the CVD device at a rate of 9 L / min, and the volume concentration of silane was controlled to be 60%. The temperature was then raised to 680°C and a vapor deposition reaction was carried out for 5 hours to obtain an active substance.

[0130] (2) The active substance and sucrose were mixed in a mass ratio of 50:45, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 920° C. for 2 h.

[0131] (3) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.

[0132] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is silicon particles, the average particle size of the silicon-based material is 3.0 nm, and the specific surface area of ​​the negative electrode material is 3.1 m 2 / g, and the median particle size is 5.5μm.

[0133] The deposition coefficient α of the vapor deposition in this embodiment is 0.51.

[0134] Example 3

[0135] (1) The starch was carbonized at 950°C for 8 h, and the carbonized product was treated with 4.6 mol / L hydrochloric acid for 7 h. After drying, a mixed gas of water vapor and nitrogen (water vapor concentration was 12.6%) was introduced, and the temperature was raised to 980°C and activated for 24 h to obtain a carbon matrix material with an average pore size of 1.5 nm and an average particle size of 6 μm.

[0136] (2) The carbon matrix material is placed in a chemical vapor deposition (CVD) device, silane is introduced into the CVD device at a rate of 29 L / min, the volume concentration of silane is controlled to be 45%, and then the temperature is raised to 700°C and a vapor deposition reaction is carried out for 3 hours to obtain an active substance.

[0137] (3) The active material and the epoxy resin were mixed in a mass ratio of 50:55, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 620° C. for 2 h.

[0138] (4) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.

[0139] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is amorphous silicon, the average particle size of the silicon-based material is 6.7nm, and the specific surface area of ​​the negative electrode material is 2.3m 2 / g, and the median particle size is 6.8μm.

[0140] The deposition coefficient α of the vapor deposition in this embodiment is 0.25.

[0141] Example 4

[0142] (1) A commercial carbon matrix material with an average pore size of 3.6 nm and an average particle size of 14 μm was placed in a chemical vapor deposition (CVD) device, and silane was introduced into the CVD device at a rate of 15 L / min, and the volume concentration of silane was controlled to be 65%. The temperature was then raised to 700°C and a vapor deposition reaction was carried out for 4 hours to obtain an active substance.

[0143] (2) The active substance and the phenolic resin were mixed in a mass ratio of 30:45, and then the mixed material was placed in a high-temperature box furnace, nitrogen was introduced, and heat-treated at 820° C. for 4 h.

[0144] (4) The obtained sample is crushed, sieved, and then classified to obtain a negative electrode material having a carbon layer on the surface.

[0145] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is nano-silicon, the average particle size of the silicon-based material is 1.9 nm, and the specific surface area of ​​the negative electrode material is 2.9 m 2 / g, and the median particle size is 9.9μm.

[0146] The deposition coefficient α of the vapor deposition in this embodiment is 0.12.

[0147] Example 5

[0148] The difference from Example 1 is:

[0149] (2) The carbon matrix material is placed in a chemical vapor deposition (CVD) device, silane is introduced into the CVD device at a rate of 22 L / min, the silane concentration is controlled to be 50%, and then the temperature is raised to 600° C. and a vapor deposition reaction is performed for 6 hours to obtain an active substance.

[0150] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is amorphous silicon, the average particle size of the silicon-based material is 2.2 nm, and the specific surface area of ​​the negative electrode material is 2.9 m 2 / g, and the median particle size is 10.0μm.

[0151] The deposition coefficient α of the vapor deposition in this embodiment is 0.39.

[0152] Example 6

[0153] The difference from Example 1 is:

[0154] (2) The carbon matrix material is placed in a chemical vapor deposition (CVD) device, silane is introduced into the CVD device at a rate of 22 L / min, the silane concentration is controlled to be 13%, and then the temperature is raised to 600° C. and a vapor deposition reaction is carried out for 4 hours to obtain an active substance.

[0155] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is amorphous silicon, the average particle size of the silicon-based material is 2.3 nm, and the specific surface area of ​​the negative electrode material is 3.2 m 2 / g, and the median particle size is 9.8μm.

[0156] In this embodiment, the deposition coefficient α of the vapor deposition is 1.0.

[0157] Example 7

[0158] The difference from Example 4 is:

[0159] (1) A commercial carbon matrix material with an average pore size of 3.6 nm and an average particle size of 14 μm was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 15 L / min, and the silane concentration was controlled to be 10%. The temperature was then raised to 700°C and a vapor deposition reaction was performed for 4 hours to obtain an active substance.

[0160] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is nano-silicon, the average particle size of the silicon-based material is 3.9 nm, and the specific surface area of ​​the negative electrode material is 3.0 m 2 / g, and the median particle size is 9.6μm.

[0161] The deposition coefficient α of the vapor deposition in this embodiment is 0.77.

[0162] Example 8

[0163] The difference from Example 4 is:

[0164] (1) A commercial carbon matrix material with an average pore size of 3.6 nm and an average particle size of 14 μm was placed in a chemical vapor deposition (CVD) device, silane was introduced into the CVD device at a rate of 17 L / min, and the silane concentration was controlled to be 10%. The temperature was then raised to 700°C and a vapor deposition reaction was performed for 4 hours to obtain an active substance.

[0165] The negative electrode material prepared in this embodiment includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is nano-silicon, the average particle size of the silicon-based material is 3.84nm, and the specific surface area of ​​the negative electrode material is 2.8m 2 / g, and the median particle size is 8.8μm.

[0166] The deposition coefficient α of the vapor deposition in this embodiment is 0.10.

[0167] Comparative Example 1

[0168] Different from Example 1, (2) the carbon matrix material is placed in a chemical vapor deposition (CVD) device, silane is introduced into the CVD device at a rate of 22 L / min, the silane concentration is controlled to be 50%, and then the temperature is raised to 600°C, and the vapor deposition reaction is carried out for 16 hours to obtain an active substance.

[0169] The negative electrode material prepared in this comparative example includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is nano-silicon, the average particle size of the silicon-based material is 3.9 nm, and the specific surface area of ​​the negative electrode material is 4.4 m 2 / g, and the median particle size is 9.4μm.

[0170] The deposition coefficient α of the vapor deposition in this embodiment is 1.04.

[0171] Comparative Example 2

[0172] The difference from Example 1 is that (1) the bamboo charcoal is carbonized at 850°C for 16 hours, and then the carbonized product is treated with 6 mol / L hydrochloric acid for 5 hours. After drying, a mixed gas of water vapor and nitrogen (water vapor concentration is 3.8%) is introduced, the temperature is raised to 720°C, and the activation treatment is performed for 16 hours to obtain a carbon matrix material with an average pore size of 5.8 nm and an average particle size of 10 μm.

[0173] The negative electrode material prepared in this comparative example includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is nano-silicon, the average particle size of the silicon-based material is 6.9nm, and the specific surface area of ​​the negative electrode material is 2.3m 2 / g, and the median particle size is 10.7μm.

[0174] The deposition coefficient α of the vapor deposition in this embodiment is 0.03.

[0175] Comparative Example 3

[0176] Different from Example 1, (2) the porous carbon matrix material is placed in a chemical vapor deposition (CVD) device, silane is introduced into the CVD device at a rate of 22 L / min, the silane concentration is controlled to be 50%, and then the temperature is raised to 850°C and the vapor deposition reaction is carried out for 16 hours to obtain the negative electrode material.

[0177] The negative electrode material prepared in this comparative example includes an active material, the active material includes a carbon-based material and a silicon-based material, the carbon-based material has pores, at least part of the silicon-based material is distributed in the pores of the carbon-based material, wherein the carbon-based material is porous carbon, the silicon-based material is nano-silicon, the average particle size of the silicon-based material is 3.8nm, and the specific surface area of ​​the negative electrode material is 3.3m 2 / g, and the median particle size is 10.3μm.

[0178] The deposition coefficient α of the vapor deposition in this embodiment is 1.04.

[0179] Test method:

[0180] (1) Testing method for specific surface area of ​​negative electrode materials:

[0181] The specific surface area was measured using the American Micromeritics TriStar 3000 specific surface area and pore size analyzer.

[0182] (2) Testing method for total pore volume of carbon matrix materials:

[0183] The test was carried out using the ASAP2460 equipment from Micromeritics, USA. The pore volume V was calculated using the BJH Desorption cumulative volume of pores model. Calculated within the pore size range.

[0184] Micromeretics ASAP 2460 was used for micropore and mesopore analysis. At liquid nitrogen temperature, the equilibrium adsorption of nitrogen on the surface of an object is related to its pore size and other characteristics. Combined with the law of the change of adsorption amount with relative pressure during adsorption, multiple models can be fitted to calculate the pore size. The report generated by the software uses density functional theory (abbreviated as DFT) method to calculate the pore size distribution, total pore volume and pore volume within a certain range.

[0185] (3) Method for testing the pore size of carbon matrix:

[0186] Take an appropriate amount of sample particles and measure the pore diameter under a transmission electron microscope (TEM).

[0187] (4) Testing method for particle size of silicon-based materials:

[0188] The nano-silicon particles are observed by a field emission scanning electron microscope or a transmission electron microscope, and the particle sizes of 5-10 nano-silicon particles are directly measured by a scale, and the average value of the particle sizes is taken as the final particle size of the nano-silicon particles.

[0189] (5) Test method for particle size of negative electrode material:

[0190] Malvern Laser Particle Sizer MS3000 is used. Based on the principle that the intensity distribution of scattered light generated by particles in all directions depends on the size of the particles, large particles have small scattering angles and small particles have large scattering angles, the particle size distribution of the particles can be obtained by using the scattered light intensity distribution of laser diffraction.

[0191] (6) Calculation method of half-peak width

[0192] Define half-width FWHM = 2[(Xp-Xl)+(XP-Xr)], where FWHM represents the half-width, Xp represents the peak position of the curve, and Xl and Xr represent the peak values ​​corresponding to the curve range (such as 200~350mV, which means the peak intensity corresponding to 200v and 350mv).

[0193] (7) Electrochemical performance test:

[0194] The following method was used to test the electrochemical cycle performance: the negative electrode materials, conductive agents and binders prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were dissolved in a solvent in a mass percentage of 94:1:5, and the solid content was controlled to be 50%, and then coated on a copper foil current collector, vacuum dried, and a negative electrode plate was obtained; then the ternary positive electrode plate prepared by the traditional mature process, 1 mol / L lithium hexafluorophosphate LiPF6 / (ethylene carbonate EC+dimethyl carbonate DMC+ethyl methyl carbonate EMC) (v / v=1:1:1) electrolyte, Celgard2400 diaphragm, and shell were assembled into 18650 cylindrical single cells using conventional production processes. The charge and discharge test of the cylindrical battery was carried out on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd. at room temperature, 0.2C constant current charge and discharge, and the charge and discharge voltage was limited to 2.75~4.2V. The first reversible capacity, first cycle charge capacity and first cycle discharge capacity were obtained. The first coulomb efficiency = first cycle discharge capacity / first cycle charge capacity.

[0195] The cycle was repeated for 50 times. The thickness of the electrode of the lithium-ion battery was measured with a micrometer and found to be H1. The expansion rate after 50 cycles = (H1-H0) / H0×100%.

[0196] Repeat the cycle for 50 cycles and record the discharge capacity as the remaining capacity of the lithium-ion battery; capacity retention rate = remaining capacity / initial capacity*100%.

[0197] The test results are shown in Table 1.

[0198] Table 1 Performance test results of negative electrode materials in various embodiments and comparative examples

[0199]

[0200] According to the data in Table 1, the negative electrode materials prepared in Examples 1 to 8 are prepared by uniformly filling the silicon-based material in the pores of the carbon-based material using a vapor deposition process. By controlling the deposition conditions, the deposition of the silicon-based material on the surface of the carbon-based material can be reduced, and the silicon-based material can be effectively filled in the pores of the carbon-based material to increase the capacity of the negative electrode material. At the same time, the size and morphology of the silicon-based material particles can be controlled to ensure that the negative electrode material can both alleviate volume expansion and maintain structural stability during the cycle, reduce the collapse of the material structure caused by volume expansion during the lithium insertion and extraction process of the negative electrode material, and effectively reduce the occurrence of side reactions between the negative electrode material and the electrolyte, thereby improving the cycle performance of the negative electrode material.

[0201] Compared with Example 1, during the preparation process of the negative electrode material of Comparative Example 1, the vapor deposition time is too long, resulting in the silicon-based material having an excessively large particle size. At the same time, the silicon-based material deposited on the surface of the carbon-based material increases, resulting in the peak B of the potential V between 380mV and 470mV becoming stronger, thereby resulting in an increase in the value of (B*F2) / (A*F1). The silicon-based material is mostly deposited on the surface of the carbon-based material rather than in the pores of the carbon-based material. The silicon-based material deposited in the pores of the carbon-based material is reduced and unevenly distributed, resulting in an increase in the volume expansion of the negative electrode material, a significant increase in the expansion rate of the pole piece, and deterioration in the cycle performance of the negative electrode material.

[0202] Compared with Example 1, during the preparation process of the negative electrode material of Comparative Example 2, the average pore size of the carbon matrix material is too large, resulting in the particle size of the silicon-based material deposited in the pores of the carbon matrix material being too large, causing the peak B at the position of 380mV~470mV to become stronger, thereby causing the value of (B*F2) / (A*F1) to increase, the deposition of silicon-based material on the surface of the carbon matrix material to increase, and the particle size of the silicon-based material deposited in the pores to be too large, resulting in a significant increase in the expansion rate of the electrode, a decrease in the structural stability of the negative electrode material, an intensification of the side reaction between the electrolyte and the negative electrode material, and a deterioration in the cycle performance of the negative electrode material.

[0203] Compared with Example 1, during the preparation process of the negative electrode material of Comparative Example 3, the temperature of vapor deposition is too high, the silicon-based material is prone to secondary growth to generate larger silicon, and the silicon-based material will transform from amorphous silicon to crystalline silicon at high temperature, resulting in the peak B at the position of 380mV~470mV becoming stronger, thereby causing the value of (B*F2) / (A*F1) to increase significantly, and the silicon-based material is difficult to deposit in the pores of the carbon-based material. The silicon-based material deposited on the surface of the carbon-based material increases significantly, resulting in a significant increase in the volume expansion of the negative electrode material and the expansion rate of the pole piece. The negative electrode material is prone to collapse of the material structure during the lithium insertion process, and the side reaction between the negative electrode material and the electrolyte is intensified, resulting in a significant deterioration in the cycle performance of the negative electrode material.

Claims

1. A negative electrode material, characterized in that: The active material comprises a carbon-based material and a silicon-based material, the carbon-based material has pores, and at least a portion of the silicon-based material is distributed in the pores of the carbon-based material; A three-electrode battery consisting of a negative electrode prepared from the negative electrode material as a working electrode, metal lithium as a reference electrode, metal lithium as a counter electrode and an electrolyte containing metal lithium ions is charged and discharged to obtain a curve graph showing the relationship between the differential value dQ / dV obtained by differentiating the charge and discharge capacity Q of the potential V of the working electrode with respect to the reference electrode and the potential V of the working electrode; In the relationship curve diagram of the differential value dQ / dV and the potential V, when the negative electrode material is energized in the delithiation direction, the differential value dQ / dV has a maximum peak value A when the potential V is between 200mV and 350mV, and the half-peak width is F1, and the differential value dQ / dV has a maximum peak value B when the potential V is between 380mV and 470mV, and the half-peak width is F2, wherein A>B and F2<F1, and the relationship is satisfied: (B*F2) / (A*F1)≤0.

35.

2. The negative electrode material according to claim 1, characterized in that It meets at least one of the following technical features: (1) The carbon matrix material includes at least one of hard carbon, soft carbon, graphite, mesophase carbon microbeads, activated carbon, porous carbon, mesoporous carbon or carbon gel; (2) The total pore volume of the carbon matrix material is ≥ 0.4 cm 3 / g; (3) The pores in the carbon matrix material include micropores, and the volume proportion of the micropores in the total pore volume is ≥ 80%; (4) The average pore size of the pores in the carbon matrix material is ≤5 nm; (5) The silicon-based material includes at least one of amorphous silicon, crystalline silicon, silicon oxide, silicon alloy, and a composite of crystalline silicon and amorphous silicon; (6) The average particle size of the silicon-based material is 1 nm to 500 nm; (7) The mass content of silicon in the silicon-based material is ≥ 99%.

3. The negative electrode material according to claim 1 or 2, characterized in that: Also included is a carbon layer located on the surface of the active material.

4. The negative electrode material according to claim 3, characterized in that It meets at least one of the following technical features: (1) The negative electrode material further includes a carbon layer located on the surface of the active material, and the carbon layer includes an amorphous carbon material; (2) The median particle size D50 of the negative electrode material is ≤10 μm; (3) The specific surface area of ​​the negative electrode material is ≤5m 2 / g.

5. A method for preparing a negative electrode material, characterized in that: The steps include: providing a carbon matrix material having pores; The carbon matrix material is vapor-deposited using a silicon source gas to obtain an active substance, wherein the negative electrode material includes the active substance, wherein the average particle size of the carbon matrix material is D μm, the average pore size of the carbon matrix material is V nm, the volume concentration ratio of the silicon source gas is H, the flow rate of the silicon source gas is NL / min, the deposition time of the vapor deposition is Th, and the deposition relationship is controlled to satisfy T*D 1 / 2 =α*V 2 *N*H, where α is the sedimentation coefficient, 0.1≤α≤1.

6. The preparation method according to claim 5, characterized in that: It meets at least one of the following technical features: (1) The silicon source gas includes at least one of monosilane, disilane, monochlorosilane and dichlorosilane; (2) The average particle size of the carbon matrix material is 1 μm to 15 μm; (3) The average pore size of the carbon matrix material is 0.1 nm to 5 nm; (4) The volume concentration of the silicon source gas is 1% to 90%; (5) The flow rate of the silicon source gas is 0.5 L / min to 100 L / min; (6) The deposition time of the vapor deposition is 0.1h to 15h; (7) The deposition temperature of the vapor deposition is 300°C to 800°C.

7. The preparation method according to claim 5, characterized in that: The step of providing the carbon matrix material with pores comprises: carbonizing the carbon source, and then acid washing and activating the carbonization product to obtain the carbon matrix material with pores.

8. The preparation method according to claim 7, characterized in that: It meets at least one of the following technical features: (1) The carbon source comprises at least one of bamboo charcoal, coconut shell, resin, starch and fruit shell; (2) the step of acid washing the carbonized product comprises: placing the carbonized product in an acid solution with a concentration of 0.5 mol / L to 15 mol / L for 0.5 h to 20 h; (3) the step of acid washing the carbonized product comprises: placing the carbonized product in an acid solution with a concentration of 0.5 mol / L to 15 mol / L for 0.5 h to 20 h, wherein the acid solution comprises at least one of hydrochloric acid, nitric acid, sulfuric acid, carbonic acid, acetic acid, benzoic acid, hydrofluoric acid, oxalic acid, phosphoric acid, and carboxylic acid; (4) the step of activating the carbonized product comprises: drying the acid-washed carbonized product and placing it in a mixed gas of nitrogen and water vapor for activation; (5) the step of activating the carbonized product comprises: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, wherein the concentration of the water vapor is 0.5% to 30%; (6) The step of activating the carbonized product comprises: drying the carbonized product after acid washing and placing it in a mixed gas of nitrogen and water vapor for activation treatment, wherein the temperature of the activation treatment is 380°C to 2000°C and the time of the activation treatment is 0.5h to 30h.

9. The preparation method according to claim 5, characterized in that: Also includes: The active material is subjected to carbon coating treatment to obtain a negative electrode material having a carbon layer on the surface; the carbon coating treatment includes at least one of solid phase carbon coating, liquid phase carbon coating and gas phase carbon coating.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared by the negative electrode material preparation method according to any one of claims 5 to 9.

Citation Information

Cited By

  • Negative electrode material and preparation method therefor, lithium-ion battery

    WO2025091988A1